Development and Initial Validation of the Need Satisfaction and Need Support at Work Scales: A Validity-Focused Approach - Susanne Tafvelin; Andreas Stenling (Scandinavian Journal of Work and Organizational Psychology, 2018)
Although the relevance of employee need satisfaction and manager need support have been examined, the integration of self-determination theory (SDT) into work and organizational psychology has been hampered by the lack of validated measures. The purpose of the current study was to develop and validate measures of employees’ perception of need satisfaction (NSa-WS) and need support (NSu-WS) at work that were grounded in SDT. We used three Swedish samples (total N = 1,430) to develop and validate our scales. We used a confirmatory approach including expert panels to assess item content relevance, confirmatory factor analysis for factorial validity, and associations with theoretically warranted outcomes to assess criterion-related validity. Scale reliability was also assessed. We found evidence of content, factorial, and criterion-related validity of our two scales of need satisfaction and need support at work. Further, the scales demonstrated high internal consistency. Our newly developed scales may be used in research and practice to further our understanding regarding how satisfaction and support of employee basic needs influence employee motivation, performance, and well-being. Our study makes a contribution to the current literature by providing (1) scales that are specifically designed for the work context, (2) an example of how expert panels can be used to assess content validity, and (3) testing of theoretically derived hypotheses that, although SDT is built on them, have not been examined before.